Effectiveness of Providing Education Using Leaflets on Knowledge and Compliance with Iron Supplement Tablet (IST) Consumption in Adolescent Girls at SMPN 1 Kromengan - Marindra Firmansyah; Gita Dwi Karisma; Yusuf Satrio Nugroho; Dinda Dwi Anggita; Faqihatul Azizah Devitasanti; Hafidh Nur Haq; Dewi Aminah (Jurnal Pengabdian Pancasila (JPP), 2025)
This study aims to evaluate the effectiveness of providing education using leaflets on knowledge and compliance with Iron Supplement Tablet (IST) consumption in adolescent girls (rematri) at SMPN 1 Kromengan, Malang. The research design used was quasi-experimental with a pre-test and post-test design in the intervention group. The study sample consisted of 50 7th grade female students selected using a purposive sampling technique conducted for 5 days. The results showed that there was a significant increase in the level of knowledge and compliance with Iron Supplement Tablet (IST) consumption after education was provided through leaflets. The average knowledge score increased from the "sufficient" category to "good" with ap value <0.05. Compliance with Iron Supplement Tablet (IST) consumption also increased significantly, with most respondents reaching the high compliance category. Education using leaflets has proven effective in increasing students' understanding of the importance of Iron Supplement Tablet (IST) consumption to prevent anemia. The conclusion of this study confirms that leaflet media can be used as a health promotion tool to increase knowledge of effective consumption of Iron Supplement Tablets in schools. Implementation of similar educational programs at a wider level is recommended to support government efforts in reducing the prevalence of anemia in adolescent girls in Indonesia.